Martha Parker’s Trials: Women’s Networks in the East India Company Trade - Brock, Aske Laursen (Journal of women's history, 2023)
This article examines how an entrepreneurial woman, Martha Parker, worked a private trade network within a globalizing world by using her connections and the East India Company’s structure to her advantage. Rather than viewing women’s independent commercial activity as a reaction to patriarchal institutions, this article pays attention to the gendered agentic expectations of early modern society, which influenced how a woman’s place in the economy was understood. Martha’s experience is supported by evidence from more than one thousand petitions to the East India Company from women, which underlines how women like Martha challenged norms and institutions. They thereby contributed to the emergence of new business practices and networks that would shape the structure and significance of private trade within the East India Company’s activities. This adds significantly to our understanding of women’s relationships to both private and corporate activity within Britain’s emerging trade and empire in Asia.